The development, implementation and validation of a plasma-based high performance liquid chromatographic assay for Isoniazid and N-Acetylisoniazid: an acetylator status population study at Brewelskloof Hospital - Cockcroft, Jennifer Jean (Division of Clinical Pharmacology, 2018)
A novel high performance liquid chromatographic assay has been developed for the simultaneous determination of isoniazid and N-acetylisoniazid in plasma. Solid phase extraction involving C18 columns is used to extract the drug and the metabolite from 0.5 ml plasma. The analyte peaks are resolved using a CB Spherisorb analytical column and ultraviolet detection at 270 nm. The assay is specific to the compounds, with consistent recovery of greater than 75% for isoniazid and over 90% for N-acetylisoniazid. The limits of detection in plasma are 300 ng/ml and 150 ng/ml for isoniazid and N-acetylisoniazid respectively. Linearity was conserved down to these concentrations. This assay was used to generate pharmacokinetic data on 114 tuberculosis patients recruited for this study at Brewelskloof hospital, Worcester, South Africa. Using these data, various markers were investigated for the determination of acetylator phenotype, namely isoniazid half-life, isoniazid plasma level at three hours, and the ratio of metabolite to drug at three hours. The ratio of metabolite to drug at three hours proved to be the most reliable method for phenotype classification, this being confirmed during the genotypic portion of the study. Trimodality was evident, although the nondiscrete separation of intermediate and rapid acetylators made this tentative. The mean values of area under the concentration-time curve for each acetylator type were found to be significantly different, with rapid acetylators being potentially compromised in terms of exposure to isoniazid (slow 32.39 mg. l⁻¹.hr, intermediate 21.25 mg. l⁻¹.hr and rapid 16.04 mg. l⁻¹.hr). Other pharmacokinetic parameters were bimodally distributed, homozygous and heterozygous rapid acetylators forming a single acetylator group. Codominance of the rapid and slow alleles was confirmed, the estimation of a mean intermediate elimination rate constant being within 7% of the observed mean. The correlation of genotype to phenotype was found to be 88.2% and the allelic distribution was determined to be acceptable using the Hardy Weinberg equation. The incidence of raised liver enzyme levels was low in the study population with no relation to acetylator phenotype. Age and weight gain after two months of daily therapy did not correlate with phenotype. The slow acetylator population comprised of a greater proportion of men, while women exhibited twice the number of rapid acetylators. No patient factors could be implicated in the apparent discordance of phenotype with genotype, and this suggests that there may be new allelic variants in this population. This report provides validation and proves the usefulness of a novel HPLC plasma-based assay for determining isoniazid and N-acetylisoniazid levels in patients with tuberculosis.